Asuhan Keperawatan pada Ny. A dengan Post Partum Sontan di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Devi Munfaiqoh; Tati Karyawati; Siti Fatimah (Lembaga Pengembangan Kinerja Dosen, 2024)
Post partum is the period after giving birth or also known as the postpartum period, namely the period needed for the uterine organs to recover to their pre-pregnancy state, the postpartum period starts from the birth of the baby and lasts for 6 weeks or 42 days (Saudah & Certainlya, 2023). The purpose of this writing is to find out and provide nursing care to Mrs. A with spontaneous post partum in the Nusa Indah room at Dr. RSUD. Soeselo, Tegal Regency. The methods used are descriptive methods and data collection methods. From the case review, it was found that the client's main complaint was that there were no complaints of occasional pain. There were two nursing diagnoses found, namely risk of infection and knowledge deficit. Interventions are structured based on theory on the SDKI, SLKI, and SIKI as well as on the client's condition and can be implemented.